Macroeconomic Challenges of Structural Transformation : Public Investment, Growth and Debt Sustainability in Sierra Leone - Balma, Lacina (IMF Working Papers; Working Paper ;, 2015)
This paper analyzes the link between public investment, economic growth and debt sustainability in Sierra Leone using an inter-temporal macroeconomic model. In the model, public capital improves the productive capacity of private capital, generating positive medium and long term effects to increases in public investment. The model application indicates that a large increase in public investment would have positive macroeconomic effects in the medium term. However, since there is no free lunch, rigidities in tax adjustment would entail unrealistic and unachievable adjustment in the current spending to cover recurrent costs and ensure debt sustainability. A more ambitious increase in public investment would entail more fiscal adjustment, particularly if external commercial loans are secured to complement the adjustment. The model simulations also emphasize the importance of improvements in the structural economic conditions to reap growth dividends. In addition, even if the macroeconomic implications of public investment scaling-up can be favorable in the long term under changes in certain structural conditions, downside risks such as terms of trade shifts and Ebola-induced productivity shortfall expose the country to increased risk of unsustainable debt dynamics. This underscores the need to remove bottlenecks to growth and maintain prudent borrowing policies.